Relevant Phytogeographic Aspects of the Pantanal (Brazil) and Considerations on the Adaptive Strategies of the Vegetation of this Biome (Research, Society and Development, 2025)
The Brazilian Pantanal, the largest tropical floodplain on the planet, forms an extensive ecotone. Recognizing the phytogeographic aspects of the Pantanal Domain is essential to understanding the ecological diversity and functional organization of its vegetation. The Paraguay River plays a central role in shaping vegetation physiognomies, controlling flood regimes and determining habitat distribution. This study aimed to analyze the phytogeographic characteristics of the Pantanal domain, seeking to identify possible adaptive strategies of vegetation to different habitats. A literature review was conducted between April and June 2025, using systematic searches in scientific databases such as ScienceDirect, SciELO, Scopus, and Web of Science. Publications from 2010 to 2025 addressing phytogeography, climate, soils, hydrology, and vegetation adaptation were prioritized. The floristic diversity of the Pantanal results from the overlap of adjacent biomes (Cerrado, Amazon, Chaco, and Atlantic Forest), topographic variability, and the hydrological regime. The vegetation is distributed among five major phytophysiognomic groups: forests, woody cerrado, herbaceous cerrado, monodominant formations, and Chaco-type vegetation, each with peculiar subdivisions. Each group exhibits specific adaptations, such as aerenchyma formation, specialized root systems, stem thickening, leaf deciduousness, and fire resistance. Additionally, the presence of endemic species in restricted microhabitats, such as saline lagoons and seasonally flooded fields, is noteworthy. It is concluded that understanding the phytogeographic patterns and adaptive strategies of Pantanal vegetation is essential to support public policies for conservation and sustainable management, especially in the face of climate change and intensified anthropogenic use.